Should ICSI be implemented during IVF to all advanced-age patients with non-male factor subfertility? - Jacob Farhi; Kfir Cohen; Yossi Mizrachi; Ariel Weissman; Arieh Raziel; Raoul Orvieto (BMC, 2019)
Abstract Backgroud In order to maximize In vitro fertilization (IVF) success rates in advanced- age patients, it has been suggested to favor the use of intracytoplasmic sperm injection (ICSI) over conventional insemination (CI), with the notion that ICSI would serve as a tool to overcome interference in sperm oocyte interaction and sperm oocyte penetration issues that can be related to maternal age and are not due to sperm abnormalities. We therefore aim to evaluate the role of ICSI in the treatment of non-male factor infertile patients aged ≥35 in terms of fertilization and top-quality embryo rates. Methods In this retrospective cohort study, data were collected and analyzed for all patients with non-male factor infertility, aged ≥35 treated, undergoing their first IVF cycle attempt with 6 or more oocytes yield, in whom a 50% ICSI-CI division was performed. Results Five hundreds and four oocytes were collected from 52 eligible patients. Overall, 245 oocytes underwent ICSI and 259 oocytes underwent CI. The fertilization rate was 71.0% following ICSI, compared to 50.1% in the CI treated oocytes (P < 0.001). The top quality embryo rate was 62.8% following ICSI compared to 45.5% following CI (P < 0.001). Subdividing the study population to two age groups revealed that the above differences remained significant in patients aged 35-39 yrs., whereas in those aged 40-45 yrs., the differences were non-significant but still inclined in favor of ICSI. Conclusions This study favors the use of ICSI in the older IVF population in order to increase both the fertilization rate and the number of top quality embryos that result per IVF cycle. Further studies are needed to establish our observations and use ICSI as the preferred approach to overcome egg sperm abnormal interactions related to advanced maternal age.